miR-18a induces myotubes atrophy by down-regulating IgfI - Liu, Chuncheng; Wang, Meng; Chen, Min; Zhang, Kuo; Gu, Lijie; Li, Qiuyan; Yu, Zhengquan; Li, Ning; Meng, Qingyong (The international journal of biochemistry & cell biology, 2017)
•Overexpression of miR-18a induces myotubes atrophy and increases the expression of MuRF1, Atrogin-1 and CTSL.•And the phosphorylation of both Akt and FoxO3 are both inhibited by miR-18a, well an inhibitor of the PI3K/Akt pathway blocks the function of miR-18a.•An analysis of miR-18a targets reveals that Igf1 is regulated by miR-18a. miR-18a suppresses the expression of Igf1 in a 3′UTR-dependent manner. Muscle atrophy occurs when there is a net loss of muscle mass, leading to a change in the balance between protein synthesis and protein degradation. Igf1 is important for protein synthesis in muscle cells and can induce local skeletal muscle hypertrophy and attenuate age-related skeletal muscle atrophy via the PI3K/Akt pathway in mice, consequently restoring and improving muscle mass and strength. In this study, we show that miR-18a expression is down-regulated during C2C12 myoblast differentiation and mouse tibialis anterior muscle postnatal development. Functional studies show that forced expression of miR-18a induces myotubes atrophy and increases the expression of MuRF1, Atrogin-1 and CTSL. miR-18a also decreases the phosphorylation of both Akt and FoxO3, and an inhibitor of the PI3K/Akt pathway blocks the function of miR-18a. An analysis of miR-18a targets reveals that Igf1 is regulated by miR-18a. miR-18a suppresses the expression of Igf1 in a 3′UTR-dependent manner. These findings strongly support the idea that miR-18a has a functional role in muscle physiology and suggest that miR-18a is a potential novel therapeutic target for skeletal muscle atrophy.